LISE - an automated analyser of business competitors - Ferreira, Nayara da Silva; Costa, Valéria Oliveira (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Nowadays, anyone with an initial idea can become an entrepreneur. But experts advise that the idea be well thought out before applying it to the market. The analysis of business competitors is one of the ways that helps the entrepreneur devise strategies to seize the market. However, the manual process of this review is time-consuming and tiring. Considering the great interaction of companies and their clients in social networks and Internet applications, this work presents LISE as a solution. This solution is a system developed to automate the process of analyzing competitors, using the application of Google Maps to collect data of the competitors of the locality that the entrepreneur wants to develop his company. As an expected contribution, this paper intends that this tool helps entrepreneurs to analyze their competitors quickly and easily..